Real Time Mask Detection Using Viola Jones Method - Safrida Ika Guslianto; Khairunnas Khairunnas; Tachiyya Nailal Khusna; Miftahul Jannah (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
The coronavirus disease (COVID-19) pandemic requires us to wear masks when doing direct contact with other people. The use of masks is mandatory in some places to break the chain of the spread of the COVID-19 virus. The spread of this virus occurs through the respiratory tract. Wearing masks is a form of our efforts to suppress the spread of this virus. This study detects human face objects in a room to determine faces that use masks and faces without using masks. The research was conducted using the Viola Jones Method in the OpenCV-Python library. This paper resulted in a good accuracy of the tests carried out to obtain 95.6% results. This detection agent has been able to perform face recognition with the condition of using a mask and the face without using a mask. On the display screen will show the face recognition accuracy in real time of the detected face object.